Studi Numerik Pengaruh Variasi Pembebanan Troli Pengangkut Barang di Laboratorium Manufaktur ITNY Terhadap Analisis Struktur Menggunakan Metode Elemen Hingga - Angger Bagus Prasetiyo; Kartinasari Ayuhikmatin Sekarjati; Iman Pradana A. Assagaf; Iqbal Rizaki Putra (Journal of Energy, Materials, & Manufacturing Technology, 2023)
In many workplaces, we frequently see people manually transporting products. Many workers who use this trolley complain about back pain, lower back sprains, shoulders, and leg injuries, which leads to accidents and lost productivity. The goal of this study is to redesign the aluminum 6061 material frame of the ITNY Manufacturing Laboratory goods transport trolley in order to reduce issues with the regular and periodic maintenance and repainting. The loading ranges are 10000N, 20000N, 30000N, 40000N, 50000N, 60000N, 70000N, 80000N, and 90000N. The approach is the finite element method. According to the trolley simulation findings, the maximum von Mises stress value increases from 81.43 MPa at 50000N to 60000N loading. The largest increase in deformation occurred at a loading difference of 2.8527mm between 50000N and 60000N. The loading simulation from 10000N to 20000N, which had a safety factor value of 3.806, saw the biggest drop. The trolley's proposed design, made of 6061 aluminum, is capable of withstanding loads up to 30000 N